Dari Ubi ke Bolu : Sosialisasi Pengolahan Ubi Ungu menjadi Bolu Kukus sebagai Strategi Peningkatan Nilai Tambah dan Pendapatan Rumah Tangga pada Kelompok Tani Pade Girang. - Ainun Jamil, Farah; Rifani Nur Sindy Setiawan; Eka Nurminda Dewi Mandalika; Ni Made Nike Zeamita Widiyanti; Shelly Sylvia Agustina (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service activity aims to increase the understanding of the Pade Girang Farmers Group about the importance of product innovation in agriculture to improve added value and family income. The socialization was held on July 4, 2025, in Landah Village, Praya Timur District, using three main stages: preparation, socialization, and monitoring and evaluation. The preparation stage included field observation and the development of materials based on the needs of the farmers. During the socialization stage, participants received information about the economic potential of processing purple sweet potatoes into steamed sponge cake, supported by visual examples and interactive discussions. The evaluation stage was carried out through questions and group reflection to understand participants’ comprehension and responses. The results showed that participants gained new knowledge about processing agricultural products into higher-value items and showed interest in developing similar products in the future. This activity became an initial step in building awareness, motivation, and innovative thinking among the farmers in managing local potential more productively.